2018
DOI: 10.1145/3197517.3201300
|View full text |Cite
|
Sign up to set email alerts
|

Fast and deep deformation approximations

Abstract: Character rigs are procedural systems that compute the shape of an animated character for a given pose. They can be highly complex and must account for bulges, wrinkles, and other aspects of a character's appearance. When comparing film-quality character rigs with those designed for real-time applications, there is typically a substantial and readily apparent difference in the quality of the mesh deformations. Real-time rigs are limited by a computational budget and often trade realism for performance. Rigs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…As for layer size and count, we found that two hidden layers of width 100 provided the best tradeoff between training accuracy and simulation speed as can be seen in Figure 6. This result mirrors that of other recent works such as [BODO18] which found only two layers to be sufficient after PCA reduction.…”
Section: Nonlinear Reduced Model Learningsupporting
confidence: 90%
“…As for layer size and count, we found that two hidden layers of width 100 provided the best tradeoff between training accuracy and simulation speed as can be seen in Figure 6. This result mirrors that of other recent works such as [BODO18] which found only two layers to be sufficient after PCA reduction.…”
Section: Nonlinear Reduced Model Learningsupporting
confidence: 90%
“…Data‐Driven Models. Multiple works, both well established [LCF00, SRIC01] and recent [BODO18, CO18], propose to model surface deformations as a function of pose. Similar to them, some existing data‐driven methods for clothing animation also use the underlying kinematic skeletal model to drive the garment deformation [KV08, WHRO10, GRH*12, XUC*14, HTC*14].…”
Section: Related Workmentioning
confidence: 99%
“…Finally, one of the more philosophical questions in deep learning seems to revolve around what should or should not be considered a "learning crime" (drawing similarities to variational crimes [45]). For example, in [2], the authors learn a perturbation of linear blend skinning as opposed to the whole shape, assuming that the perturbation is lowerdimensional, spatially correlated, and/or easier to learn. The authors in [18,41] use spatially correlated networks for spatially correlated information under the assumption, once again, that this leads to a network that is easier to train and generalizes better.…”
Section: Discussionmentioning
confidence: 99%